IMPLEMENTASI KEBIJAKAN E-RETRIBUSI PASAR GOTONG ROYONG DALAM MENINGKATKAN PENDAPATAN KEUANGAN DAN ASET DAERAH KOTA PROBOLINGGO - Astuti, Veronica Sri; Mubarok, Husni; ., Arifin (Universitas Panca Marga, 2022)
Regional autonomy provides additional authority for regional governments to manage all regional affairs and interests in a more independent manner. This autonomy policy gives authority to the regions to regulate and manage the interests of the local community, explore sources of finance and local revenue for the city of Probolinggo. Market retribution is a form of payment charged to users who occupy shops to carry out economic transactions in the market area. The E-levy policy is a solution provided by the government in managing fees by implementing an internet-based information technology system. The type of research used is qualitative by using the method of observation and direct interviews with respondents. So it can be seen that the implementation of E-levies in the mutual cooperation market in increasing financial income and regional assets of the city of Probolinggo is not optimal. The focus of this research was conducted on Gotong Royong Market traders in Probolinggo City who occupy Bedak. The results of this study indicate that there is no difference in the implementation of the Gotong Royong Market E-Retribution policy in Probolinggo City. While the factors that influence the sustainability of implementing the e-retribution program in the mutual cooperation market are only influenced by the factor of traders who lack awareness in paying levy taxes.